2020
DOI: 10.1002/acn3.51014
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations of Erdheim–Chester Disease

Abstract: Objective: To characterize the spectrum of neurologic involvement in Erdheim-Chester Disease (ECD), a treatable inflammatory neoplasm of histiocytes. Methods: Sixty-two patients with ECD were prospectively enrolled in a natural history study that facilitated collection of clinical, imaging, laboratory, neurophysiologic, and pathologic data. Results: Ninety-four percent of the patients had neurologic abnormalities on examination or imaging, and 22% had neurologic symptoms as the initial presentation of ECD. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 40 publications
6
19
0
Order By: Relevance
“…Referring to previous studies, clinical and radiologic features of ECD with CNS involvement and TE are summarized in Table . In our case, the clinical presentations of cerebellar ataxia, abnormal mental status, and cognitive change were compatible with both diseases (8)(9)(10)(11)(12)(13). Regarding MRI findings, previous studies have reported similar types of abnormalities in both diseases, including nodular lesions, diffuse T2-hyperintense lesions, and brain Key clinical and radiologic features of Erdheim-Chester disease (ECD) with central nervous system (CNS) involvement and toxoplasmic encephalitis (TE) with comparison between previous studies and our case (8)(9)(10)(11)(12)(13). MRI: magnetic resonance imaging, N/A: not available atrophy (9)(10)(11)(12)(13).…”
Section: Figure 3 Other Radiologic Findings On 99m Tc-mdp Bone Scinti...supporting
confidence: 60%
“…Referring to previous studies, clinical and radiologic features of ECD with CNS involvement and TE are summarized in Table . In our case, the clinical presentations of cerebellar ataxia, abnormal mental status, and cognitive change were compatible with both diseases (8)(9)(10)(11)(12)(13). Regarding MRI findings, previous studies have reported similar types of abnormalities in both diseases, including nodular lesions, diffuse T2-hyperintense lesions, and brain Key clinical and radiologic features of Erdheim-Chester disease (ECD) with central nervous system (CNS) involvement and toxoplasmic encephalitis (TE) with comparison between previous studies and our case (8)(9)(10)(11)(12)(13). MRI: magnetic resonance imaging, N/A: not available atrophy (9)(10)(11)(12)(13).…”
Section: Figure 3 Other Radiologic Findings On 99m Tc-mdp Bone Scinti...supporting
confidence: 60%
“…Additionally, CNS involvement was an independent, poor prognostic factor for mortality in ECD subjects at five years in their study [18]. Neurologic symptoms can be the presenting feature of ECD, and given the mean delay in ECD diagnosis of 4.2 years, ECD must be considered in patients with inflammatory, infectious or neoplastic-appearing white matter [26]. Clinicians treating ECD should be aware of the high prevalence of API and the association between CNS lesions and mortality.…”
Section: Discussionmentioning
confidence: 96%
“…Central nervous system involvement in ECD remains a major cause of morbidity and mortality [26]. For instance, a survival analysis of 53 cases of ECD reported CNS involvement in 51%; these were directly responsible for 29% of reported deaths [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations